Analisis Pengawasan dan Profesionalitas Apron Movement Controller (AMC) pada Bandara Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan - ASHYA KHAERUNIDA; Dwi Agustina (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of this study was to determine the conditions, obstacles, and efforts/solutions related to the supervision and professionalism of Apron Movement Controller (AMC) employees at Sultan Aji Muhammad Sulaiman Sepinggan Airport, Balikpapan. The concept used in this study is supervision and professionalism. This research was conducted at Sultan Aji Muhammad Sulaiman Sepinggan Airport, Balikpapan, from April 2021 to August 2021. The results of this study are that employees of the AMC Unit at Sultan Aji Muhammad Sulaiman Sepinggan Airport, Balikpapan, have shown good supervision and professionalism, the obstacles that exist in companies such as: a) The minimum number of supervisors so that the workload piles up; b) Officials are difficult to contact; c) Self-decision making, and efforts made to overcome obstacles that can be carried out by employees: a) Opening job vacancies; b) Promotion; c) Education and training.